Comparison of the Volatile Constituents of Pelargonium quercetorum Agnew. of Iran with Some of the Other Pelargonium Species - (Arman) Taherpour, Avat; Kheradm, Khojasteh (Asian Journal of Chemistry, 2010)
In this study, the volatile constituents of the essential oil of Pelargonium quercetorum Agnew. were investigated and compared with some of the other species of Pelargonium. Pelargonium quercetorum Agnew. is one of the Pelargonium genus of that was collected from Kurdistan area in Iran. Twenty six components in the essential oil of Pelargonium quercetorum Agnew. representing twenty one of the total oils were identified by GC and GC/MS technique. In this herb, α-pinene (25.28 %), α-fenchyl acetate (20.63 %) have the most percentages among compounds of the essential oil. Some other components like limonene (9.94 %), β-caryophyllene (8.20 %) are located in the second level of the concentration in the essential oil.